Incidence of overwork-related mental disorders and suicide in Japan. (12th June 2018) - Yamauchi, T; Sasaki, T; Yoshikawa, T; Matsumoto, S; Takahashi, M
Abstract: Background: Mental disorders and suicide resulting from overwork or work-related stress have become major occupational health issues worldwide, particularly in Asian countries. However, no studies have reported incidence rates of mental disorders and suicide by sex, age group and industry, using a national database containing all cases involving compensation in Asian countries. Aims: The present study examined incidence rates of occupational mental disorders and suicide by sex, age group and industry using a database containing all cases involving compensation for mental disorders and suicide in Japan over a 5-year period. Methods: Cases involving compensation for mental disorders and suicide in Japan between January 2010 and March 2015 were analysed. Incidence rates over the 5-year study period were calculated by sex, age group and industry. Results: In total, 1990 cases involving compensation for mental disorders and suicide (619 women and 1371 men) between January 2010 and March 2015 were analysed. The incidence rate involving compensation was higher in employees aged between 30 and 39 years. In men, incidence rates were higher in 'accommodation/eating/drinking services', 'information/communication' and 'scientific research, professional and technical services'. In these industries, incidence rates were particularly high for those aged 29 years or younger. Conclusions: Our findings highlight the importance of promoting mental health support for younger employees and increasing awareness of their working conditions. Differences in incidence rates by sex, age and industry should be taken into consideration in the development of a national policy and industry- and age-specific preventive measures for overwork-related mental disorders and suicide.